2017
DOI: 10.5306/wjco.v8.i2.106
|View full text |Cite
|
Sign up to set email alerts
|

Leptin signaling and cancer chemoresistance: Perspectives

Abstract: Obesity is a major health problem and currently is endemic around the world. Obesity is a risk factor for several different types of cancer, significantly promoting cancer incidence, progression, poor prognosis and resistance to anti-cancer therapies. The study of this resistance is critical as development of chemoresistance is a serious drawback for the successful and effective drug-based treatments of cancer. There is increasing evidence that augmented adiposity can impact on chemotherapeutic treatment of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 183 publications
(206 reference statements)
1
45
0
1
Order By: Relevance
“…A wide-used PC drug, gemcitabine, increased PCSC expressing CD24+ and CD133+, stemness-associated genes (Bmi1, Nanog, and Sox2), cell migration, chemoresistance, and tumorigenesis [ 51 ]. Gemcitabine induced PCSC overexpressing ABCB1 and CD44+ that correlated with higher tumor histological grade and worse prognosis [ 3 ]. Moreover, Notch2, Notch4 and JAG1 overexpression correlated with PC-Gemcitabine chemoresistance [ 70 ].…”
Section: Notch Pathway and Pc Chemoresistancementioning
confidence: 99%
See 2 more Smart Citations
“…A wide-used PC drug, gemcitabine, increased PCSC expressing CD24+ and CD133+, stemness-associated genes (Bmi1, Nanog, and Sox2), cell migration, chemoresistance, and tumorigenesis [ 51 ]. Gemcitabine induced PCSC overexpressing ABCB1 and CD44+ that correlated with higher tumor histological grade and worse prognosis [ 3 ]. Moreover, Notch2, Notch4 and JAG1 overexpression correlated with PC-Gemcitabine chemoresistance [ 70 ].…”
Section: Notch Pathway and Pc Chemoresistancementioning
confidence: 99%
“…It is known that leptin and Notch signaling mediate the activation of cancer stem cells that can affect drug resistance [ 3 , 54 , 95 ]. We have further shown that leptin and its receptor OB-R are expressed on PC cells, establishing an autocrine/paracrine signaling loop [ 37 ].…”
Section: Notch Pathway and Adipokines In Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of leptin and its receptor, the ObR, has been associated to tumor progressionrelated events in breast cancer [4][5][6]. Leptin exerts its effects through binding with the ObR receptor, promoting the activation of several signaling pathways such as MAPK, PI3K/AKT and JAK/STAT [3,7,8]. The signaling pathways activated by leptin regulate cell proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) [4,5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-apoptotic and mitogenic effects of leptin have been demonstrated on different cancer cell lines [ 19 ]. From reports, the significantly high circulating level of leptin is associated with enhanced cell proliferation and increased risks of cancers in the leptin resistance in obese subjects [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%